(untitled) (Global Journal of Science Frontier Research, 2023)
The devolution of power and resources by the State to local authorities much en vogue today in Cameroon and other areas of the world is fast becoming a governance model which could be relied upon for the assertion and articulation of communities based land management and ownership rights